Higher Education e-Learning Usability Analysis Using System Usability Scale - Didi Supriyadi; S. Thya Safitri; Daniel Yeri Kristiyanto (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
The COVID-19 pandemic encourages almost every institution to optimize the use of information and communication technology to maintain consistency and competitive advantage. One of the efforts made by Higher education is developing and optimizing online-based learning (e-learning) models. E-learning plays an important role in the success of achieving learning objectives at Telkom Institute of Technology Purwokerto (ITTP), which is conducted between lecturers and students. The problem faced in optimizing e-learning system at ITTP is related to usability. The purpose of this study is to evaluate the usability level of the ITTP e-learning system using the System Usability Scale (SUS) method. Based on the testing of questionnaire instruments using SPSS software, it was obtained the result that the questionnaire used for the study was valid, and the reliability rate was 0.758. Based on the results of system tests to 100 respondents or users, it is known that the SUS score is 55.3. The value indicates that the acceptability ranges are in the Marginal Low range. It can be seen from the adjective rating, SUS score from the ITTP e-learning system is in the CATEGORY OK and according to Curved Grade Scale (CGS) is in grade D. Based on Net Promoter Scale (NPS), the score 55.3 indicates that the ITTP e-learning system users tend to be in the Detractor category.